Is the Timber Construction Sector Prepared for E-Commerce via Instagram®? A Perspective from Brazil - Araujo, Victor de [UNESP]; Švajlenka, Jozef; Vasconcelos, Juliano [UNESP]; Santos, Herisson; Serra, Sheyla; Almeida Filho, Fernando; Paliari, José; Lahr, Francisco Rocco; Christoforo, André (MDPI, 2022)
Timber construction is a contemporary solution where sales are performed through in-store trade. Timber house e-commerce may stimulate global markets, and in times of intense remote routines, it is useful to improve the performance of the wood and construction sectors. Timber housing producers and dealers are the research object under analysis to study the electronic market of this Brazilian sector on Instagram®. With just over four hundred companies, nearly 80% of this sector already utilizes this virtual social network. We validated the outcomes through a significant sampling of all 315 companies with corporate profiles to identify their competences, goals, and failures. The profiles prioritize the elucidation of products and basic features, not yet being ready for the virtual sales of timber houses. The study makes it clear that our results typify a sector marked by a developing electronic market. Inserting a description of product prices and detailed specifications may change this status. From failures and competences, a classification for social profiles was proposed to measure the progress and virtual participation of each individual.
Keywords: construction market; sectoral survey; timber house; wood promotion